MANUFACTURING TECHNOLOGY ADOPTION AMONG LEAN MANUFACTURERS: AN INITIAL STUDY (Journal of Technology and Operations Management, 2012)
Lean manufacturing is a technique that allows work to be performed without bottlenecks or delays while eliminating wasteful activities by linking and balancing equal amounts of work steps together, enabling products to be consumed directly into the next step, one piece at a time until completed. The aim of this research is to analyse the level of implementation of manufacturing technology among lean practitioners in Malaysia. It highlights on the types of technologies applied in the lean practice and to what extend the level of technologies being used. A questionnaire survey was used to identify the different manufacturing technologies being used and the level of applications among lean manufacturers in Malaysia. From the questionnaire results, it shows that there are 3 groups of manufacturing technology used by manufacturers, mainly the direct, indirect and administrative technology. Meanwhile, according to the results the level of technologies used by lean manufacturers in Malaysia is considered as within medium level. This might be due to the cost of applying such technologies or the lack of information regarding each manufacturing technologies